Imaginer un lycée, un exercice aux Beaux-Arts - Anne-Marie Châtelet (In Situ)
What role did the high schools play in the training of architects at the École des Beaux-Arts?This question might sound odd if you don’t bear in mind that the education was mainly based on competitive spirit and that it consisted in training students for building projects design. It was only through regular participation in the architectural design competitions they were offered that these students could progress with their studies. Each month, different kind of subjects were entrusted to them, with varying difficulty and nature. This review examines the frequency of lycées and collèges (France’s high schools and middle schools) among this wide range of subjects, from the beginning of the 19th century to the dissolution of the École des beaux-arts in 1968, a period which also saw the development of the lycées whose creation dates from 1802. On several occasions, the professor of theory or the Académie d’Architecture, that had the privilege of determining the Prix de Rome, opted in favour of a secondary educational establishment, and it generally coincided with a significant moment in the evolution of these buildings. The judging criteria for the submitted projects vacillated between mastery of the composition rules and knowledge of what was being built at the time. Thus, the students received awards for their design virtuosity or for their adroitness in interpreting a well-proven solution, more rarely for their ability to suggest forward-looking ideas.